Simulating the impact of the global economic crisis and policy responses on children in West and Central Africa - Cockburn, John; Fofana, Ismaël; Tiberti, Luca (Palgrave Macmillan, 2012)
In Children in crisis: Seeking child-sensitive policy responses, ed. Caroline Harper, Nicola Jones, Ronald U. Mendoza, David Stewart; and Erika Strand. Part II Emerging evidence on the impact of the 2008–10 crises. Chapter 5. Pp. 75-92.